Study on the Change Law of Pore Structure and Permeability of Coal Under Chemical Permeability Enhancement Technology - Wang, Guan; Tai, Dezhi (International Journal of Natural Resources and Environmental Studies, 2024)
In order to deeply explore the permeability enhancement effect and permeability enhancement mechanism of the three chemical permeability enhancement technologies, the pore structure change and permeability enhancement mechanism of anthracite coal were studied from the perspective of coal pore structure. The following conclusions are drawn: the permeation effect of the four solutions from large to small is 99% CS2, 10% NaClO, 8% HF, 8% The total pore volume of HCl and HCl solution decreases after acidification, the pore volume of HF solution increases after acidification, the number of pores in the coal sample after oxidation of NaClO solution increases, and the micropores are transformed into mesopores, and the pore volume of CS2 solution increases after extraction, and the pore expansion effect is better than that of the other three solutions, and the pore volume with a pore diameter greater than 2 nm affects the flow of gas between pores, and the larger the pore volume, the higher the permeability. The pores with a pore diameter of less than 2 nm have little correlation with the permeability of coal and rock, and the micropores do not affect the gas flow